Keputusan pembelian konsumen buku k13 PT Gramedia di Indramayu, Jawa Barat di tinjau dari perspektif brand equity dan relationship marketing - Kamaludin, Ahmad; Muhammad Iqbal Nurfauzan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of brand equity and relationship marketing on consumer purchasing decisions for 2013 curriculum books at PT. Gramedia marketing area of Indramayu Regency. The research method used is descriptive quantitative with explanatory survey design. The population in the study was junior high school who purchased the 2013 curriculum books, totaling 75 schools. Collecting data using a questionnaire containing instruments or indicators for analysis. The data analysis technique used is multiple regression with t test and F test to test the research hypothesis. The results showed that brand equity and relationship marketing have a positive and significant influence on consumer purchasing decisions for 2013 curriculum books at PT. Gramedia marketing area of Indramayu Regency either simultaneously or partially. The limitation of this study is that the independent variables cannot provide comprehensive answers to answer purchasing decision problems. Research findings are empirical evidence that can be used as a review to improve purchasing decisions or relevant management topics.